Transformation of political culture in the process of social democratization of states during transitional period - Krasiwski, Orest; Parubchak, Ivan (Studia Europaea Gnesnensia, 2014)
The phenomenon of political culture has been considered as the basis for stability and dynamic development of thestate. Correlation between functioning of democratic institutions and transformation of political culture in the country has been studied. Forms have been investigated and stages of social democratization at the present time have been analyzed. The role of political and cultural factors in the evolutionary processes of social democratization has been substantiated.